The Meaning Construction of a Scientific Approach on Teaching Islamic Education - S.A.P, Rangga Sa’adillah; Tobroni; Ishomuddin; Khozin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to describe and analyze the scientific approach model carried out by Islamic Religious Education teachers in SMA Sidoarjo. This research uses the constructivist paradigm by using phenomenology as its research approach. Through structural data analysis using four stages including 1) description of the phenomenon; 2) horizonalization; 3) cluster of meaning; and 4) a description of the essence obtained by the results of the study as follows. Teachers of Islamic Education teachers’ understanding of the steps in the scientific approach has not been maximized so that it has implications for the application of scientific approach models that only reach the quasi stage of discovery learning, problem-based learning, and project-based learning. Although the teacher’s understanding is still not perfect and the application of the scientific approach at the level of the quasi model, the scientific approach taken by the teachers meets the rules of the scientific process. The findings of this study are Islamic Religious Education teachers applying the Burhani approach in the learning process of Islamic Religious Education